Literature Review of the Art of Humble Inquiry Concept and the Od Process Consulting: Dual Tools for Peak Organizational Performance for Positive Business Results - Nyakora, Prof. Musa (Social Science Learning Education Journal, 2016)
To learn the art of humble inquiry requires experience and training in interpersonal skills, organizational development processes, facilitation, and coaching.Â  Skills needed include: listening and asking questions, being assertive, influence skills, showing empathy, observation skills, confronting the client when needed, giving balanced feedback, drawing out the clientsâ thoughts and emotions, making process or procedural suggestions, redirecting the client, summarizing, debriefing, and gaining agreement and commitment.To genuinely help a client, the OD Process Consultant must realize his role as the âhelperâ not the âexpertâ or âdoctorâ.Â  Too often consultants think they know the solution to the problem based on their previous experience.Â  However, an OD Process Consultantâs role is to build the client relationship, gain their trust, be curious and listen, and to use humble inquiry to help the client understand and solve their own problems.The Main purpose of this article, therefore, is to take the readers through the memory lane of different authors who have made an impact on creating awareness regarding the existing literature on humble inquiry concept and its impact on organizational performance towards positive business results.